Once Upon a Mastodon - Worth, Bonnie; Ruiz, Aristides; Mathieu, Joe, 1949- (New York : Random House, 2014)
The Cat in the Hat embarks on a whirlwind tour of Pleistocene animals, introducing species ranging from mastodons and mammoths to woolly rhinos and saber-toothed cats.
Includes bibliographical references (page 43) and index.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile literature; Mammals, Fossil -- Juvenile literature; Glacial epoch -- Juvenile literature; Cat in the Hat (Fictitious character); Mammals, Fossil; Glacial epoch